The Importance of Discharge Planning in Stroke Patients: Literature Review - Anie Tri Indiartinie; Eppy Setiyowati; Yurike Septianingrum; Abdul Muhith; Ima Nadatien; Umdatus Soleha; Rusdianingseh (Universitas STRADA Indonesia, 2023)
Background: Stroke causes neurologic disturbances that can cause changes in quality of life. Quality of life is mental, physical, social health and regardless of disease. In order to achieve a good quality of life, there must be a role for health workers. Discharge planning in stroke patients is preparing patients for treatment in healing and improving the health status of stroke patients. Purpose: The purpose of the literature review is to find out the importance of discharge planning in stroke patients. Methods: The research stage is to make a selection by paying attention to the year of publication and with full text. Furthermore, articles and journals that are considered less relevant are excluded. Literature was obtained from 10 articles relevant to Google Scholar, Indonesia One Search, DOAJ, and Garuda with the keywords Discharge planning, Quality of life and Stroke. Results: After reviewing the selected articles, it was found that discharge planning has a good impact on increasing family readiness in caring for patients, as well as improving the quality of life of stroke patients, namely being able to increase rehabilitation activities, prevent disease complications and adherence to taking medication and routine control. Conclusions: Improving the quality of life of stroke patients, which can improve rehabilitation activities, prevent disease complications and comply with taking medication and routine control.